Developing stakeholders in the circular supply chain of EV batteries: Initiate strategy - Ramadhan, Iqbal; Purwani , Annie (OPSI, 2025)
The significant increase in the number of electric vehicles has led to the accumulation of used battery waste. This waste has the potential to pollute the environment, so a solution in the form of battery recycling (repair, refurbishment, reuse) is needed. However, this effort is hampered by the availability of workshops capable of recycling electric batteries. This study aims to identify and analyze the factors that influence repair shops' intentions to recycle electric batteries. These factors were collected through an open questionnaire classified based on the PESTEL framework, then the weight of each factor's importance was determined using the AHP method to formulate the initiation of electric vehicle battery recycling growth. The study prioritized the factors contributing to repair shops' intention to recycle batteries as follows: economic, technological, social, and environmental factors. The order of priority of these factors was then formulated as an initiation strategy: developing technological infrastructure and training, providing green certification, tax breaks and financial support, producer responsibility policies, and building partnerships. This research makes an important contribution to initiating strategies to address electric vehicle battery waste through a systematic approach in Indonesia.